Potentially Preventable Hospitalizations for Chronic Conditions among Youth. (30th September 2020) - Sentell, T; Choi, S Y; Ching, L; Uchima, O; Keliikoa, L B; Irvin, L; Pirkle, C
Abstract: Objective: Chronic, preventable conditions like diabetes and hypertension previously seen primarily in adults are increasing among young people. Chronic disease-related potentially preventable hospitalizations (PPH) are costly. The study goal was to quantify potentially preventable hospitalizations (PPH) for chronic disease in those aged 5-29 years in one diverse state of the USA. Methods: With Hawai'i statewide inpatient 2015-2016 data across all payers, we used standard metrics to capture asthma, diabetes, and hypertension PPH. Denominators were obtained by age group, gender, race/ethnicity, and living in O'ahu vs. other Hawaiian Islands from American Community Survey data. A multivariable negative binomial regression model predicted having a PPH adjusting for age group, gender, race/ethnicity, and O'ahu residency. Results: Six percent (775) of inpatient hospitalizations among young people, representing 455 unique individuals, were PPH for a chronic disease. The types of PPH inpatient hospitalizations include diabetes (436), asthma (261), heart disease (64) and hypertension (14). The number of PPH visits per individual ranged from 1-20 with a mean of 1.7 (SD: 2.28) visits. The total cost of these PPH during this 2-year time period was 16, 762, 262. Among unique individuals with a chronic disease PPH (N = 455), the mean age was 17.5 (SD: 8.2); 55% were male. In the multivariable model, those who were between 10-14 years (RR:0.47;0.32-0.69) and 15-19 years (RR:0.46;0.31-0.69) were significantly less likely to have a PPH compared to those aged 5-9 years. Other Pacific Islanders were significantly more likely to have a PPH (RR: 3.08; 2.05-4.63) compared to whites. Conclusions: Many hospitalizations by those aged 5-29 years were PPH. Pacific Islander youth had PPH chronic disease disparities. Chronic disease prevention and management is critical. Solutions may include equitable chronic disease prevention policies and improving access to culturally relevant care. Key messages: This study reveals important disparities in youth that may lead to future health risks as well as current poor outcomes. Other Pacific Islanders were at significantly increased risk for PPH for chronic disease compared to other racial/ethnic groups from early childhood to young adulthood.